Evolving Hyper Heuristic-Based Solvers for Rush Hour and FreeCell - Hauptman, Ami; Elyasaf, Achiya; Sipper, Moshe (Proceedings of the International Symposium on Combinatorial Search, 2010)
We use genetic programming to evolve highly successful solvers for two puzzles: Rush Hour and FreeCell.